2011
DOI: 10.1074/mcp.m111.009753
|View full text |Cite
|
Sign up to set email alerts
|

A Perturbed Ubiquitin Landscape Distinguishes Between Ubiquitin in Trafficking and in Proteolysis

Abstract: Any of seven lysine residues on ubiquitin can serve as the base for chain-extension, resulting in a sizeable spectrum of ubiquitin modifications differing in chain length or linkage type. By optimizing a procedure for rapid lysis, we charted the profile of conjugated cellular ubiquitin directly from whole cell extract. Roughly half of conjugated ubiquitin (even at high molecular weights) was nonextended, consisting of monoubiquitin modifications and chain terminators (endcaps). Of extended ubiquitin, the prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(132 citation statements)
references
References 123 publications
7
121
0
4
Order By: Relevance
“…However, the amount of proteins that are single ubiquitinated was not assessed in this case. A different study also performed in yeast showed that 56% of all ubiquitin modified proteins are either monoubiquitinated or have an end-cap ubiquitin, and the remaining bulk is given to polyubiquitin modified proteins (Ziv et al, 2011). In this case the relative abundance of different types of polyubiquitin chains was quite different from the early observations in yeast: the K48 polyubiquitin chains were once again the most prevalent ones (21%), followed by K63 (18%), K29 (5%), K11 (0.6%), K33 ($0.1%) and K27 ($0.1%), while K6 was not detected (Ziv et al, 2011).…”
Section: Ubiquitinmentioning
confidence: 99%
“…However, the amount of proteins that are single ubiquitinated was not assessed in this case. A different study also performed in yeast showed that 56% of all ubiquitin modified proteins are either monoubiquitinated or have an end-cap ubiquitin, and the remaining bulk is given to polyubiquitin modified proteins (Ziv et al, 2011). In this case the relative abundance of different types of polyubiquitin chains was quite different from the early observations in yeast: the K48 polyubiquitin chains were once again the most prevalent ones (21%), followed by K63 (18%), K29 (5%), K11 (0.6%), K33 ($0.1%) and K27 ($0.1%), while K6 was not detected (Ziv et al, 2011).…”
Section: Ubiquitinmentioning
confidence: 99%
“…Proteomic studies reveal that each of the isopeptide linkage types is represented to a significant extent in both yeast and mammalian cells (54,117,196,282,298). The attachment of ubiquitin chains with any isopeptide linkage excepting Lys63 appears to target substrates to the proteasome in vivo (54,172).…”
Section: Introductionmentioning
confidence: 99%
“…Cell extracts were prepared from log-phase cells using a TCA lysis method (Ziv et al 2011). Eighty micrograms of total protein were loaded on SDS-PAGE.…”
Section: Western Blottingmentioning
confidence: 99%
“…The heavy (H)-SILAC-labeled cells were then continuously exposed to 0.01% MMS to induce replication stress, and the light (L)-SILAC-labeled cells were mock-exposed. After 3 hr, heavy and light cells were harvested and lysed using a previously described trichloroacetic acid (TCA) lysis method (Ziv et al 2011). To ensure reproducibility, the entire experiment was repeated, and the labels were swapped such that the (L)-SILAC-labeled wild-type yeast cells were exposed to 0.01% MMS for 3 hr, and the (H)-SILAC-labeled wild-type yeast cells were mock-exposed.…”
Section: Quantitative Ms Screen For Mmsresponsive Phosphopeptidesmentioning
confidence: 99%